Gender-Based Violence Againsts The Female Main Character in Colleen Hoovers It Ends With Us - Taria Ayu Lestari; Agnes Setyowati; Tetty Yukesti (Universitas Pakuan, 2019)
Abstract This research is a study of Colleen Hoovers novel It Ends With Us. The purpose of this study is to reveal forms and impacts of gender-based violence and efforts of the female main character to overcome all the hardship. The main issue in this novel is gender-based violence againts the female main character named Lily Bloom. In this research, descriptive analysis method is used in studying the intrinsic theories, and extrinsic theories such as gender and feminism for supporting elements. The findings of this research points that Lily experiences several forms of gender-based violences such as child abuse, physical attacks, domestic violence, pornography violence, and an act of rape. Besides that, the physical and psychological impacts are also identified. Eventually, Lily can overcome her hardship by improving her financial condition, living independently, divorcing her abusive partner, and becoming a single parent. Both internal and external factors are in support of her measure to survive and live a better life. Keywords: feminism, gender, gender-based violence, women